2017
DOI: 10.1096/fj.201700389r
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Western diet age‐specifically alters female offspring voluntary physical activity and dopamine‐ and leptin‐related gene expression

Abstract: Prenatal overnutrition affects development into adulthood and influences risk of obesity. We assessed the transgenerational effect of maternal Western diet (WD) consumption on offspring physical activity. Voluntary wheel running was increased in juvenile (4-7 wk of age), but decreased in adult (16-19 wk of age), F female WD offspring In contrast, no wheel-running differences in F male offspring were observed. Increased wheel running in juvenile female WD offspring was associated with up-regulated dopamine rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…66 Maternal Western diet during pregnancy was associated with increased locomotor activity in juvenile female offspring, while adult female, but not male, offspring demonstrated decreased locomotor activity. 69 to controls, consistent with increased anxiety. [71][72][73][74][75][76][77] Anxiety-like behavior in offspring of obese dams has also been noted in the morris water maze task, open field test, and light-dark transition tests.…”
Section: Hyperactivitymentioning
confidence: 68%
See 2 more Smart Citations
“…66 Maternal Western diet during pregnancy was associated with increased locomotor activity in juvenile female offspring, while adult female, but not male, offspring demonstrated decreased locomotor activity. 69 to controls, consistent with increased anxiety. [71][72][73][74][75][76][77] Anxiety-like behavior in offspring of obese dams has also been noted in the morris water maze task, open field test, and light-dark transition tests.…”
Section: Hyperactivitymentioning
confidence: 68%
“…Rodent studies have shown increased locomotor activity in the offspring of obese dams, although data are conflicting regarding which sex is more affected by this exposure. 66,69,70 Male offspring exposed to a maternal HFD demonstrated increased hyperactivity in the open field test, which was not corrected by maternal dietary intervention during lactation. 66 Maternal Western diet during pregnancy was associated with increased locomotor activity in juvenile female offspring, while adult female, but not male, offspring demonstrated decreased locomotor activity.…”
Section: Hyperactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetics, such as DNA methylation, may be involved in the impact the western diet has on the human body. The effects of maternal Western diet on offspring physical activity, gene expression, and phenotype were assessed in [ 44 ]. Interestingly, differences in F1 female offspring but not in F2 male and female offspring were observed, suggesting that changes in the F1 generation were related to in utero somatic reprogramming.…”
Section: Nutritional Epigeneticsmentioning
confidence: 99%
“…To determine the role of reducing NAc neuronal activity on voluntary wheel-running behavior in an inducible fashion, a separate set of TA B L E 1 Listing of primary antibodies used have been successfully used in our laboratory (Grigsby et al, 2018;Ruegsegger et al, 2017). Following injections, incisions were closed using tissue adhesive (Vetbond, 3M, Maplewood, MN), and rats were allowed to recover on a 32°C heating pad until ambulatory.…”
Section: Aav-2 Nac Expression Of Hm4di-dreaddsmentioning
confidence: 99%